DIPLOMASI INDONESIA DI KAWASAN PASIFIK SELATAN PADA MASA PEMERINTAHAN JOKO WIDODO TAHUN 2015-2019 - Silvia Rahmadani; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research explains Indonesia's diplomacy in the South Pacific region during the period of Joko Widodo (Jokowi) in 2015-2019. Geographical proximity and the existence of cultural similarities make the South Pacific region has an important meaning in Indonesian geopolitics. In addition, Indonesia has a national interest to protect the sovereignty of the Republic of Indonesia regarding the issue of Papuan separatism which is a concern in the region.The research method used in this research is a qualitative method with data collection techniques through document analysis. The level of analysis used in this research is the level of system analysis. This research uses the theory of The Adaptive Model in analyzing foreign policy carried out by Jokowi.Based on the research results obtained, it can be concluded that Jokowi approached the South Pacific region as an adaptive action to protect the sovereignty of the Republic of Indonesia from the support of South Pacific countries for Papuan independence. External changes that occurred in the South Pacific forced Jokowi to adjust foreign policy to defend Indonesia's national interests (Acquiscent Adaptation). Jokowi implements a policy of Looking East and uses economic diplomacy and cultural diplomacy to build good relations between Indonesia and the South Pacific region.Keywords: Diplomacy, Indonesia, South Pacific Region, Foreign Policy, Separatism.